Use of drugs that induce osteoporosis or fracture in older adult with myeloma multiple: cross-sectional study - Mariany Lara ROSA; Cristiane Menezes DE PÁDUA; Taisa Lopes MACHADO; Paula Lana DRUMMOND; Lívia Pena SILVEIRA; Jéssica Soares MALTA; Adriano Max REIS (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2023)
Objective: to describe the frequency of use of medications that induce osteoporosis or fracture (MOF) by old adult with multiple myeloma and evaluate associated factors. Methods: cross-sectional study, developed in three settings: a public teaching hospital, a private outpatient onco-hematology service, a public hospital, reference in oncology. Data were collected between April 2019 and March 2020 by means of face-to-face interviews and review of patients' medical records. The dependent variable was the use of MOF. The drugs were identified in pharmacovigilance studies conducted from the Japanese database of adverse drug event reports and the World Health Organization's Vigibase that calculated the reporting odds ratio (ROR) of osteoporosis or fracture for the drugs. Factors associated with MOF by patients of study use were determined by multiple logistic regression. The drugs were classified by the fourth level of Anatomical Therapeutic Chemical (ATC) Classification. Results: 153 older adult (≥ 60 years) were included, with a median age of 70.9 years, female predominance (54.2%), and 73.2% of the older adult were using at least one MOF. Most of the older adult (56.9%) were seen in the private health service. The most common comorbidity was hypertension (67.3%), followed by diabetes mellitus (28.8%). The most frequent MOF were proton pump inhibitors (PPIs) (29.2%) and sulfonamides (13.9%) followed by benzodiazepine related drugs (11.9%) and other opioids (10.4%). The older adult who used MOF presented the following characteristics: age up to 70 years, female gender, income up to three salaries, high education (high school or higher), multimorbidity, hypertension and polypharmacy. In multivariate analysis, an independent and positive association was obtained between MOF use and polypharmacy, MOF and high education. Conclusion: the frequency of MOF use by the older adult studied was high and was positively and independently associated with polypharmacy and high education. The ATC classes of MOF with the highest frequency of use were: PPIs, high-ceiling diuretic (sulfonamides), benzodiazepines related drugs and other opioids.